Peningkatan Kemampuan Ibu Dalam Penataan Menu Sehat Balita Untuk Mencapai Status Kesehatan Prima Di Rejowinangun - Lastariwati, Badraningsih; Komariah, Kokom; Hamidah, Siti; Sugiyono, Sugiyono; M, Endang (Prosiding Pendidikan Teknik Boga Busana, 2020)
The purpose of this activity is 1 ) to improve the mother in healthy menu draw based on the program piringku balita.2 ) improved the skills to mother in processed vegetable process and presenting for toddlers .3 ) improved the skills mother in process and presenting fruit to meal balita.4 ).Improved the skills mother in process and presenting an pauk for toddlers. Method used is lectures, activities integration, demonstration, and training ( both the individual practice ), and and discussion.Lectures and integration used to describe hygiene and environment; individual knowledge and healthy menu, processing and presentation of.activities used to practice behavior, tackling , food handling waste held, processing techniques, and presentationn of food, a discussion used to understand the problems faced by partner The results of the activities of practice which can be done with practice ten culinary menu that includes: takoyaki, vegetables tempe, rolade vegetables the nuggets teme, tempe, sticks ,rice omerice, vegetables broil, fruit miscellaneous, fruit pudding ,vegetable croquet cassava sentiling and madusari.The results were applied as follows: activity increase arrangement toddlers, healthy menu through drawing up a menu for one round in 10 days for toddlers healthy achieved 80 % processed .cooking culinary menu for toddlers healthy with indicator tilling practices some herrings, for toddlers Cultivate processed fruits and vegetables achieved 80 % .presentation toddlers reorganize and provides healthy food eating with beautiful, Healthy and interesting achieved 80 % Based on the response of participants benefit to evaluate the performance of material about the techniques draw up the menu healthy for toddlers 3,9 very beneficial , a vegetable processing 3,8 very useful for toddlers , process and presenting side dish 3,8 very useful for toddlers , manner of presenting a fruit for toddlers 3,8 very useful and knowledge on the contents 3,9 . Inctructur matter by this very very well , used either training strategy , the speakers very well . Keywords: increased,the mother ability,toddler menu arrangemen